Fitosociología del bosque de galería del río Conceição en el Ecomuseo del Cerrado, Goiás (Brasil) - Imaña-Encinas, José (2022)
The Cerrado is a vast biome (1.8 million km²) of great richness and heterogeneity, and it is also one of the most threatened ecosystems in the world. Its conservation depends on studies that support a rational management. Within the Cerrado, the riparian forest is environmentally valuable and very extensive, but it is highly degraded. The breast height diameters and the botanical identification of the living trees in two sampling plots (2000 m2) of riparian forest in a protected area of the Cerrado were obtained. 279 trees from 32 families, 46 genera and 54 species were surveyed. 30% of the species belonged to only three families (Rubiaceae, Chrysobalanaceae and Myrtaceae). The Shannon-Wiener diversity index (H‘ = 3.09 nats/ind.) was lower than other references and the distribution of the specimens by species was relatively homogeneous (equability equal to 0.77). Nine species accumulated about 52% of the total abundance value index (IVI), highlighting Hirtella gracilipes and Licania apetala, which accounted for more than 35% of the individuals. The basal area (27 m²/ha), density (1395 ind./ha) and quadratic mean diameter (15.8 cm) were similar or lower than those reported for other Brazilian riparian forests. The total diameter distribution was decreasing, with diameters generally below 20 cm. It was a young community with natural regeneration capacity, although decreasing diameter distributions were hardly found by species. Changes are expected due to a reduction in the presence of species with insufficient regeneration (Calophyllum brasiliense, Guettarda viburnoides, Sclerolobium paniculatum and Xylopia emarginata).